The impact of a One Laptop per Child Program on learning: Evidence from Uruguay - Gioia de Melo; Alina Machado; Alfonso Miranda (Banco de México, 2014)
We present evidence on the impact on students' math and reading scores of one of the largest deployments of an OLPC program and the only one implemented at a national scale: Plan Ceibal in Uruguay. We have unique data that allow us to know the exact date of laptop delivery for every student in the sample. This gives us the ability to use days of exposure as a treatment intensity measure. Given that there is some variation in the date of laptop delivery across individuals within the same school, we can identify the effect of the program net of potential heterogeneity in the rate schools gain improvements on students' achievement over time independently of the OLPC program. Our results suggest that in the first two years of its implementation the program had no effects on math and reading scores. The absence of effect could be explained by the fact that the program did not involve compulsory teacher training and that laptops in class were mainly used to search for information on the internet. – – En este artículo se presenta evidencia sobre el impacto en los puntajes de matemáticas y lectura del programa Un Computador por Ni\~no con mayor despliegue y el único implementado a escala nacional: el Plan Ceibal en Uruguay. Se cuenta con información única que nos permite conocer la fecha exacta de entrega de la laptop para cada estudiante de la muestra. Ello habilita a utilizar los días de exposición al Plan Ceibal como una medida de la intensidad del tratamiento. Dado que la entrega de la laptop exhibe cierta variación al interior de las escuelas, es posible aislar el efecto del programa de una potencial heterogeneidad en la tasa a la que, independientemente del programa, las escuelas logran mejoras en el desempe\~no de sus estudiantes. Nuestros resultados sugieren que en los primeros dos a\~nos de su implementación, el programa no tuvo efectos en los puntajes de matemáticas y lectura. Esto podría explicarse por el hecho de que el programa no implicó capacitación obligatoria para los docentes y que en clase las laptops se utilizaban principalmente para buscar información en internet.
Keywords: I21; I28; 330; technology; education; impact evaluation